Pendaftaran Peralihan Hak Atas Tanah Warisan Yang Belum Dibagi - Ati Rahmawati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
The government, in an effort to ensure legal certainty, is holding registration of land rights, and registrants are given letters as strong evidence. The registration in question includes the transfer of land rights to the National Land Agency. The transfer of land rights occurs due to inheritance of registered land rights, which must be submitted by those who receive the rights to the land in question as inheritance to the Land Office, a certificate of title in question, a death certificate of the person whose name is recorded as the holder of the rights and a certificate of proof as an expert. inheritance, as in Article 42 PP No. 24 of 1997 concerning Land Registration. Registration of the transfer of land rights includes the requirements for a death certificate of the person whose name is recorded as the holder of the rights and a letter of proof of being the heir, as in Article 111 of the Regulation of the Minister of State for Agrarian Affairs/Head of the National Land Agency Number 3 of 1997 which has been amended by the Regulation of the Minister of Agrarian Affairs/Head of BPN No. 16 of 2021. The Yogyakarta Land Office is processing the transfer of names of inherited land parcels that have not been divided. According to the BPN's statement in the trial, the provisions for changing the name of the certificate have been carried out in accordance with the correct procedures. Keywords: Registration of Transfer of Rights; Inherited Land; Not Yet Divided.